Characteristics of Pb2+ doped CsI matriz under gamma and neutron excitations - Maria da Conceição Costa Pereira; Maria da Conceição Costa Pereira; Tufic Madi Filho; José Roberto Berretta; Lucas Faustino Tomáz; Marlene Cristina Pinto (Brazilian Journal of Radiation Sciences, 2019)
In recent years, there has been an increasing interest in finding new fast scintillating material or improve the characteristics of known scintillators for the demand of high energy physics, industrial and nuclear medical applications. Ions divalent lead Pb2+ built in some crystal structures are efficient emission centers and their applications in scintillators was and still is the reason of an intensive study of emission properties of different compounds containing these ions. In this context, the crystals of Pb2+ doped CsI matrix were grown by the vertical Bridgman technique and subjected to annealing in vacuum of 10-6 mbar and continuous temperatura of 350°C, for 24 hours, and then they were employed. To evaluate the response of the CsI:Pb scintillator crystal to gamma radiation, radioactive sources of 137Cs (662 keV), 60Co (1173 keV and 1333 keV), 22Na (511 keV and 1275 keV) and 133Ba (355 keV) was used. The operating voltage of the photomultiplier was 2700 V for the detection of gamma rays and the accumulation time in the counting process was 600 s. The scintillator response to neutron radiation from a radioactive source of Am/Be with energy range of 1 MeV to 12 MeV was available. The activity of the AmBe source was 1Ci Am. The fluency was 2.6 x 106 neutrons / second. The operating voltage of the photomultiplier tube was 1300 V. The accumulation time in the counting process was 600 s. With the results obtained, it may be observed that the crystals are sensitivetothese radiations.